Structure of physical activity in inhabitants of the Moravian-Silesian region between 2005-2009 with regard to formal length of education - Igor Fojtík; Josef Mitáš (Palacký University Olomouc, 2012)
BACKGROUND: Regular physical activity is an important factor in human health status. The fact, that the physical activity will be regular, is influenced by many internal and external individual factors. Education is considered to be an important factor that influences physical activity. There has not been fully clarified the relationship between physical activity and education in pursuit of regional indicators yet. AIM: The aim of this study was to analyze the physical activity of adult inhabitants of the Moravian-Silesian region with regard to the number of years spent in formal education. METHODS: The research sample consisted of 759 residents of MoravianSilesian region (419 women and 340 men) aged 25-58. The IPAQ questionnaire was used to obtain the data, which was distributed by trained university students in the spring and autumn periods of 2005-2009. Kruskal Wallis ANOVA test was used for the statistical evaluation of the data. The eﬀect size was calculated to clarify the internal diﬀerences in results. RESULTS: Significant diﬀerences in the structure of physical activity were found only in men in the job related physical activity (H = 6.277; p = 0.05; η2 = 0.019) and in vigorous physical activity (H = 6.230; p = 0.05; η2 = 0.018). Physically most active are men with lowest level of education. No significant diﬀerence was found in the monitored parameters for women. Job related physical activity means the highest part of the total physical activity in respondents with lowest education. CONCLUSION: The results of the survey point to the fact, that diﬀerent level of education is not an important factor associated with physical activity in Moravian-Silesian region. To promote physical activity we would recommend focusing on physical activity in leisure time, during transport and on vigorous physical activity in all groups of respondents based on educational level.